(untitled) (Indonesian Journal of Civil Engineering Study, 2026)
Flooding caused by high-intensity rainfall is a common issue in the Punden Arum residential area, located in Kedunguter Village, Karangtengah District, Demak Regency. This problem has prompted the search for effective solutions to reduce the risk of flooding in the area. This study aims to analyze the effectiveness of infiltration wells (resapan wells) in mitigating floods. The analytical methods used include field surveys, hydrological analysis, and infiltration well capacity analysis. The study is based on local rainfall parameters and appropriate design considerations. The hydrological analysis showed that the runoff discharge for a Type 45 house with an area of 846 m² is 0.85 m³/second for a 2-year return period, 1.00 m³/second for a 5-year return period, and 1.07 m³/second for a 10-year return period. Meanwhile, the calculation of the area’s total runoff discharge, which includes both residential and road catchment areas with a total area of 958 m², results in a discharge of 1.23 m³/second for the 10-year return period, based on the runoff coefficient (C) value. The planned infiltration wells are designed with a height of 2 meters and a radius of 0.5 meters (1-meter diameter), resulting in a total storage volume of 15.7 m³ and an infiltration discharge of 2.261 m³. In the study area, a total of 10 infiltration wells are planned, capable of accommodating a total rainwater runoff volume of 17.961 m³. The results of the infiltration well planning indicate that the design is effective in retaining rainwater runoff in the study area, as the total storage volume of the infiltration wells exceeds the required runoff volume.